Late quaternary organic carbon and biomarker records from the Laptev Sea continental margin (Arctic Ocean): implications for organic carbon flux and composition. - Stein, Ruediger; Fahl, Kirsten; Niessen, Frank; Siebold, Martina (PANGAEA, 1999)
In order to understand the processes controlling organic carbon deposition (i.e., primary productivity vs. terrigenous supply) and their paleoceanographic significance, three sediment cores (PS2471, PS2474. and PS2476) from the Laptev Sea continental margin were investigated for their content and composition of organic carbon. The characterization of organic matter indudes the determination of buk parameters (hydrogen index values and C/N ratios) and the analysis of specific biomarkers (n-alaknes, fatty acids, alkenones, and pigments). Total organic carbon (TOC) values vary between 0.3 and 2%. In general, the organic matter from the Laptev Sea continental margin is dominated by terrigenous matter throughout. However. significant amounts of marine organic carbon occur. The turbidites, according to a still preliminary stratigraphy probably deposited during glacial Oxygen Isotope Stages 2 and 4, are characterized by maximum amounts of organic carbon of terrigenous origin. Marine organic carbon appears to show enhanced relative abundances in the Termination I (?) and early Holocene time intervals, as indicated by maximum amounts of short chain n-alkanes, short-chain fatty acids, and alkenones. The increased amounts of faity acids, however, may also have a freshwater origin due to increased river discharge at that time. The occurrence of alkenones is suggested to indicate an intensification of Atlantic water inflow along the Eurasian continental margin starting at that time. Oxygen Isotope Stage l accumutation rates of total organic carhon are 0.3, 0.17, and 0.02 C/cm**2/ky in cores PS2476, PS2474, and PS2471, respectively.
Organic carbon and biomarker record from the Laptev Sea continental margin
Keywords: Amundsen Basin; ARK-IX/4; ARK-VIII/3; AWI_Paleo; Gakkel Ridge, Arctic Ocean; Giant box corer; Giant piston corer; GKG; GPC; Gravity corer (Kiel type); KAL; Kasten corer; Laptev Sea; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; Polarstern; PS19/157; PS19/165; PS19 ARCTIC91; PS2163-4; PS2170-3; PS2471-4; PS2474-2; PS2474-3; PS2476-3; PS2476-4; PS27; PS27/054; PS27/059; PS27/062; Quaternary Environment of the Eurasian North; QUEEN; SL